Continuous Quality Improvement - Advancing Understanding of Design, Application, Impact and Evaluation of CQI Approaches - Edward Broughton (Frontiers Research Topics, 2017)
Continuous Quality Improvement (CQI) methods are increasingly widely used to bridge the gaps between the evidence base for best clinical practice, what actually happens in practice, and the achievement of better population health outcomes. Among a range of quality improvement strategies, CQI methods are characterised by iterative and ongoing use of specific processes to identify quality problems, develop solutions, and implement and evaluate changes. The application of CQI processes in health is evolving and evidence of their success continues to emerge. There is, however, a need to enhance understanding of how best to implement, scale-up and evaluate CQI programs for the purpose of improving quality of care and population health outcomes in different contexts. This research topic aims to attract articles that add to knowledge of useful approaches to tailoring CQI methods for different contexts or purposes, and for implementation, scale-up and evaluation of CQI interventions/programs.